Dragon Slayer's Academy : Beware! It's Friday the 13th - McMullan, Kate; Basso, Bill (New York : Grosset & Dunlap, 2006)
Upon superstitious headmaster Mordred's orders, the returning students and new lasses of Dragon Slayers' Academy deck themselves in lucky charms on Friday the thirteenth, but luck may not help when a wicked dragon arrives seeking revenge.
Keywords: Dragons -- Fiction; School stories; Superstition -- Fiction; Scary stories; Juvenile fiction